Assessing Retractions in Indian Science: An Analysis of Publications from the Past Three Decades Using the Web of Science Database - Mukherjee, Bhaskar; Tiwari, Priya (DESIDOC Journal of Library & Information Technology, 2025)
The growth in the number of retracted publications in academic fields suggests that the problem is not but rather reflective of broader challenges in the research environment. This study seeks to address these concerns by focusing specifically on the trends and characteristics of retracted papers in Indian scientific publications. We examine the trend through 3162 retracted publications that appeared during 1990-2024 indexed in Web of Science database. It was observed that although a number of retracted publications were present in 1990 to 2016, the increase was more after 2016 and was highest in 2022, before declining in 2023. Most of these publications were published under collaborative authorship and 38.52 % publications came under international co-authorship with 66 countries including Ethiopia, Saudi Arabia, China, USA and received 13.60 citations per publication. There were 25.93 % publications published through institutional funds and 45.47 % publications appeared in non-OA journals. Subjects like computer science (fields like internet of things, machine learning, deep learning), medical science (apoptosis, oxidative state, covid-19), material science (nanotechnology, nano-tubes, polymer science) are the major three disciplines in where most of retractions were noticed. Highest number of retracted publications appeared in the journals having IF range 5.0 to 9.99 followed by 3.0 to 3.99. The rate of retracted articles did not necessarily decrease with increase of impact factor suggesting greater scrutiny of high-profile publications does not have an impact on retraction. Plagiarism was found as one of the major reasons for retraction followed by compromised peer review, emphasizing the need for stricter regulatory frameworks and better research practices.